2023
DOI: 10.1111/ipd.13065
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to dental fear from childhood to adolescence: A 10‐year cohort study

Abstract: BackgroundDental fear affects children's oral health; there is, however, no evidence regarding the pathways linking possible predictors for its occurrence.AimThis study aimed at exploring the direct and indirect effects of sociodemographic, clinical, behavioural and psychosocial factors on the development of dental fear in schoolchildren over time.DesignThis is a prospective cohort study, with 10 years of follow‐up. The first assessment started in 2010 (T1) with a sample of 639 children aged 1–5 years from Sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…Structural equation modeling (SEM) appears as an alternative allowing to consider multiple mediators and post-and base confounders (i.e., covariates influencing the exposure and the mediator association with outcome, respectively) to improve inference using observational studies [17][18][19]. Studies considering subjective measures of oral health as outcome already adopted the use of SEM previously [20][21][22][23]. In counterpart, considering objective measures of oral health in general, just in the recent years, this analysis was widespread, and few studies could be found [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Structural equation modeling (SEM) appears as an alternative allowing to consider multiple mediators and post-and base confounders (i.e., covariates influencing the exposure and the mediator association with outcome, respectively) to improve inference using observational studies [17][18][19]. Studies considering subjective measures of oral health as outcome already adopted the use of SEM previously [20][21][22][23]. In counterpart, considering objective measures of oral health in general, just in the recent years, this analysis was widespread, and few studies could be found [23][24][25].…”
Section: Introductionmentioning
confidence: 99%